Flavivirus RNAi suppression: decoding non-coding RNA - Pijlman, Gorben P (Current opinion in virology, 2014)
•Flaviviruses actively replicate in invertebrate cells in the face of an effective antiviral RNAi response.•The existence of viral suppressors of RNAi in arboviruses is controversial.•RNAi is suppressed by flavivirus replication in mammalian and insect cells.•Non-coding, subgenomic flavivirus RNA (sfRNA) displays RNAi suppressor activity. Flaviviruses are important human pathogens that are transmitted by invertebrate vectors, mostly mosquitoes and ticks. During replication in their vector, flaviviruses are subject to a potent innate immune response known as antiviral RNA interference (RNAi). This defense mechanism is associated with the production of small interfering (si)RNA that lead to degradation of viral RNA. To what extent flaviviruses would benefit from counteracting antiviral RNAi is subject of debate. Here, the experimental evidence to suggest the existence of flavivirus RNAi suppressors is discussed. I will highlight the putative role of non-coding, subgenomic flavivirus RNA in suppression of RNAi in insect and mammalian cells. Novel insights from ongoing research will reveal how arthropod-borne viruses modulate innate immunity including antiviral RNAi.